A forewing of the Jurassic dragonfly Austroprotolindenia jurassica Beattie & Nel (Odonata: Anisoptera) from the Talbragar Fish Bed, New South Wales, Australia. Issue 4 (2nd October 2017) - Nel, André; Frese, Michael; McLean, Graham; Beattie, Robert
Abstract : Nel, A., Frese, M., Mc Lean, G. & Beattie R., May 2017. A forewing of the Jurassic dragonfly Austroprotolindenia jurassica from the Talbragar Fish Bed, New South Wales, Australia. Alcheringa 41, 532–535. ISSN 0311-5518. The discovery of a well-preserved dragonfly forewing in the Upper Jurassic Talbragar Fish Bed near Gulgong and attributed to Austroprotolindenia jurassica Beattie & Nel allows this taxon to be placed in Protolindeniidae. It extends the palaeogeographical distribution of this family, previously known only from the Jurassic of Europe, to Australia. André Nel [ anel@mnhn.fr ], CNRS UMR 7205, CP 50, Entomologie, Muséum National d'Histoire Naturelle, 45 rue Buffon, F - 75005, Paris, France; Michael Frese [ michael.frese@canberra.edu.au ], University of Canberra, Institute for Applied Ecology and Faculty of Education, Science, Technology and Mathematics, Bruce, ACT 2601, Australia; Graham McLean [ mcleangg@bigpond.com ], The Australian Museum, 1 William St., Sydney, NSW 2010, Australia; Robert Beattie [ rgbeattie@bigpond.com ], The Australian Museum, 1 William St., Sydney, NSW 2010, Australia.